MANAJEMEN SEKOLAH BERASRAMA DALAM PEMBENTUKAN KARAKTER DAN KEMANDIRIAN SISWA DI SMA FRATER MAKASSAR - ramadhani, awaliyah ramadhani (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
This study examines and analyzes the management of the SMA Frater Makassar dormitory in shaping student character and independence. Using a qualitative approach with primary data from interviews and observations, the study found that SMA Frater Makassar implements an inclusive organizational structure based on religious and humanistic values. The school also implements a student-centered and freedom-based curriculum, as well as structured dormitory facilities and extracurricular activities. These elements collectively contribute to the holistic development of students, despite challenges such as limited dormitory capacity.